Vitality detection from biometrics: State-of-the-art - Singh Y.N.; Singh S.K. (My University, 2025)
Biometric authentication systems have become the basis of trust to human society from the beginning of last decade, but the security of the system can be breached by presenting a non-live or fake biometric sample which is the cloned of a legitimate user's identity. Different techniques have been proposed to address the problem of vitality detection from biometrics but these techniques are far away from the final solution. This paper proposes a classification of vitality detection techniques for fingerprint, face and iris biometrics for summarizing the current state-of-the-art and presents a critical review of them. We evaluate the potential of multimodal techniques of vitality detection from biometrics and analyze the performance of different vitality detection techniques on the datasets and the test conditions that have used. The use of physiological signals that have the inherited feature of vitality signs as a supplementary information with other conventional biometrics can offer a potential defense against spoofing attacks in the system. © 2011 IEEE.